Including matily herbal and spices mix in Indian diet may reduce complications of COVID-19 infection in the general population - Eapen, John Thottukadavil (International Journal of Research in Medical Sciences, 2021)
Coronavirus is a pandemic affecting the world over, cause human deaths, morbidity and causing economic loss due to frequent lockdowns. The virus mediates injury to multiple organs leading to micro- and macro vascular thrombosis. Aspirin shows promise for treatment of adult COVID-19 patients because of its anti-inflammatory properties and antithrombotic properties. We can take aspirin only under medical supervision. Against such a backdrop, there is a need to find out alternative sources of substances which act like aspirin and yet a component in the everyday diet. “Salicylic acid, the main active ingredient in aspirin, is “ubiquitously present in fruits and vegetables,” the highest concentrations are found in herbs and spices’ this drew our attention to study the role of salicylates in human nutrition. Salicylate consumption varies in different populations depending on the cuisine and methods of food preparation. Therefore, we developed a herbal mix comprising ingredients with high salicylates, to supplement it in the Indian diet. The herbal mix can be prepared in any kitchen in India. We trust adequate salicylate intake in the Indian population may reduce complications of COVID-19, in case of any infection